2016
DOI: 10.1039/c6ra09274h
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Pt nanoparticles with molecular components in polymer electrolyte membrane fuel cells: multi-scale modeling approach

Abstract: Three phase model consists of Pt nanoparticles, Nafion, and graphite with oxygen, water, and hydronium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…We used the parameters reported by Brunello et al as the vdW parameters that describe metal and nonmetal electrode systems. 46 The total potential energy is given by…”
Section: Computational Detailsmentioning
confidence: 99%
“…We used the parameters reported by Brunello et al as the vdW parameters that describe metal and nonmetal electrode systems. 46 The total potential energy is given by…”
Section: Computational Detailsmentioning
confidence: 99%
“…The results of this investigation also shed light on further possibilities for computational research on fluorinated carbon-based materials.The DFT calculations were conducted using the Biovia DFT package DMol3 [11], considering the generalized-gradient-approximation (GGA) as well as the Perdew-Burke-Ernzerhof (PBE) exchange and correlation functionals with the double numerical polarized basis set. The GGA-PBE functional has been successfully used to describe the interaction between organic molecules and a carbon-based substrate [12][13][14][15][16][17][18] or an inorganic substrate [19][20][21][22][23]. We used a 5 × 5 × 1 Monkhorst-Pack k-point mesh [24] with a 12.30 Å × 12.30 Å × 15.00 Å periodic boundary condition for the graphene substrate.The adsorption energy (E ads ) was defined aswhere E substrate+gas represents the energy of the entire system, E substrate is the energy of the substrate system alone, and E gas is the energy of the isolated gas molecule.…”
mentioning
confidence: 99%
“…Several molecular dynamics (MD) revealed that ionomer tends to form a thin layer on the surface of catalyst due to specific interactions. [169,170] The group of Jang [171] calculated the binding energies of Nafion with Pt nanoparticles using quantum mechanical DFT and molecular dynamics. It is inferred that sulfonate groups tend to be chemisorbed while CF 3 CF 3 and CF 3 OCF 3 tend to be physisorbed.…”
Section: Interactions With Catalystmentioning
confidence: 99%